April in Spain : a novel [large type] - Banville, John (Black, Benjamin, 1945- Quirke novel., 2023)
"On the idyllic coast of San Sebastian, Spain, Dublin pathologist Quirke is struggling to relax, despite the beaches, cafés and the company of his disarmingly lovely wife. When he glimpses a familiar face in the twilight at Las Acadas bar, it's hard at first to tell whether his imagination is just running away with him. Because this young woman can't be April Latimer. She was murdered by her brother, years ago--the conclusion to an unspeakable scandal that shook one of Ireland's foremost political dynasties. Unable to ignore his instincts, Quirke makes a call back home to Ireland and soon Detective St. John Strafford is dispatched to Spain. But he's not the only one en route. A relentless hit man is on the hunt for his latest prey, and the next victim might be Quirke himself" --